High-intensity curvilinear movements’ relevance in semi-professional soccer: An approach from principal components analysis - Pino-Ortega, José; Clemente, Filipe Manuel; Palucci Vieira, Luiz H [UNESP]; Rico-González, Markel (SAGE Publications, 2021)
Due to the high number of variables reported from tracking systems, the interest in data reduction techniques has grown. To date, principal component analysis (PCA) has been performed in soccer, but since the results depend on the variables included, a lack of objectivity continues to be of concern. The aim of this study was to highlight the variables that compose the principal components (PC) in semi-professional soccer, including all variables extracted from tracking systems. Data were collected from a semi-professional Spanish team that participated in 10 matches. From more than 250 variables, the PCA grouped a total of 19 variables in six PCs, explaining 72% of players’ external load. All variables were related to centripetal force, high intensity running, and high-intensity efforts and short efforts. Interestingly, the first PC was composed of four variables related to centripetal force. The current exploratory analysis indicated that, in addition to traditional high-intensity displacement variables, force measures should also be considered in soccer match analysis due to their effect on a player’s external load.
Keywords: big data; data analytics; external load; Principal component analysis; running; soccer